Placental expression of the angiogenic placental growth factor is stimulated by both aldosterone and simulated starvation - Eisele, Nicole; Albrecht, Christiane; Mistry, Hiten D.; Dick, Bernhard; Baumann, Marc; Surbeck, Daniel; Currie, Gemma; Delles, Christian; Mohaupt, Markus; Escher, Genevieve; Gennari-Moser, Carine (Elsevier, 2016)
Aldosterone is an important factor supporting placental growth and fetal development. Recently, expression of placental growth factor (PlGF) has been observed in response to aldosterone exposure in different models of atherosclerosis. Thus, we hypothesized that aldosterone up-regulates growth-adaptive angiogenesis in pregnancy, via increased placental PlGF expression.